2000
DOI: 10.1128/jb.182.21.6272-6276.2000
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli Reference Collection Group B2- and Uropathogen-Associated Polymorphism in the rpoS-mutS Region of the E. coli Chromosome

Abstract: Chromosomal DNAs of enterohemorrhagic, uropathogenic, and laboratory attenuated Escherichia coli strains differ in the rpoS-mutS region. Many uropathogens lack a deletion and an insertion characteristic of enterohemorrhagic strains. At the same chromosomal position, they harbor a 2.1-kb insertion of unknown origin with a base composition suggestive of horizontal gene transfer. Unlike virulence determinants associated with urinary tract infection and/or neonatal meningitis (pap or prs, sfa, kps, and hly), the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…In comparison to E. coli MG1655, previous studies (14,21,39) revealed that EPEC, EHEC, and E. coli group B2 strains harbor specific DNA insertions within the mutS-rpoS intergenic region. A PCR assay was developed to determine the nature of the mutS-rpoS intergenic region of the afa-8 isolates.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to E. coli MG1655, previous studies (14,21,39) revealed that EPEC, EHEC, and E. coli group B2 strains harbor specific DNA insertions within the mutS-rpoS intergenic region. A PCR assay was developed to determine the nature of the mutS-rpoS intergenic region of the afa-8 isolates.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA sequences of the rpoS loci in strains HU734 and CFT073 were determined as described by Culham & Wood (2000).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification and DNA sequence analysis revealed that the rpoS gene is present in both HU734 and CFT073 (see Methods). In comparison with E. coli K-12, both harboured a DNA insertion downstream from rpoS (Culham & Wood, 2000) as well as single base changes within rpoS. One single base change would create an amino acid change within RpoS (Q45E).…”
Section: Properties Of Pyelonephritis Isolates Hu734 and Cft073 : Rpomentioning
confidence: 99%
“…A region covering most of stem-loop 1 and the following single-stranded part of DsrA is complementary to an upstream "antisense element" in rpoS mRNA that is assumed to base pair with the TIR region, suggesting that DsrA functions by an "anti-antisense" mechanism that disrupts intramolecular basepairing in rpoS mRNA (119,120,131). DsrA plays only a minor role for rpoS translation in cells grown at 37 or 42°C yet becomes the major stimulating factor at 30°C and especially at 20°C (199). The basis of low-temperature translational induction of S is the clearly enhanced transcription of dsrA as well as a sixfoldincreased stability of DsrA at low temperature (177).…”
Section: Trans-acting Factors Involved In Rpos Translationmentioning
confidence: 99%
“…Downstream of rpoS, however, variations are quite common and even occur between different E. coli strains (28,37,83). However, nlpD can occur alone in bacteria that do not possess an rpoS gene, such as Haemophilus influenzae (55).…”
Section: Promoters Contributing To Rpos Transcriptionmentioning
confidence: 99%